Forests, Biomass Use and Poverty in Malawi - Bandyopadhyay, Sushenjit (World Bank, Washington, DC, 2012)
In this paper, the authors seek to answer three questions about poverty and forests in Malawi: (1) What is the extent of biomass available for meeting the energy needs of the poor in Malawi and how is this distributed? (2) To what extent does fuelwood scarcity affect the welfare of the poor? (3) How do households cope with scarcity? In particular, do households spend more time in fuelwood collection and less time in agriculture in response to scarcity? The authors attempt to answer these questions using household and remote-sensing data. They find that 80 percent of rural poor households in Malawi are likely to benefit from an increase in biomass per hectare in their community. Rural women respond to biomass scarcity by increasing the time they spend on fuelwood collection. But the actual decrease in consumption expenditure and increase in time in fuelwood collection are small and biomass scarcity is not associated with a reduction in agricultural labor supply.